Qualidade de vida em idosos de dois programas da Universidade Federal do Amazonas - Mesquita, Rhanna Moraes (Brasil, 2025)
Objective: To analyze the quality of life of the elderly in two programs at the Federal University of Amazonas. Method: a descriptive, cross-sectional study with a quantitative approach, which was carried out with 14 elderly people registered in two programs at the Federal University of Amazonas, from May to June 2024. Two data collection instruments were used: a form designed for the study, and a second called the World Health Organization Quality of Life Assessment (WHOQOL-bref). The data was analyzed using descriptive and inferential statistics. Results: The study concludes that elderly women, aged between 60 and 69, brown, and Catholic are the ones who participate most in the programs' activities. When assessing the quality of life of the elderly, 57% responded that they perceived it as very good or good. Conclusion: It was concluded that programs aimed at the health of the elderly contribute to a better quality of life in the emotional, psychological and social aspects of the elderly.